Speaking of Yangzhou : a Chinese city, 1550-1850 - Finnane, Antonia (Harvard East Asian monographs, 2004)
This is in some ways a biography of a city that acquired a personality, even a gender, and became an actor in its own history. The author examines the city's place in the history of the late imperial era and of the meanings that accrued to Yangzhou.